Effect of volatile organic compounds from vehicle emission on human health - Verner, Jan; Sejkorová, Marie; Hurtová, Ivana (Kaunas University of Technology, 2017)
The uncompleted combustion of automotive fuels is the causes to increase the concentration of oxides of nitrogen, oxides of carbon, unburned hydrocarbons, soot or volatile organic compounds. The paper presents the results effect of selected volatile organic compound especially BTEX (Benzene, Toluene, Ethylbenzene, m, p, o - Xylenes) on the health of passengers in cabin vehicle during different driving modes. The measurement was carried out in April and May of 2016 from city of Brno - the second biggest city in the Czech Republic. The results of measurement were processed by statistical methods and on the base of the calculations there was estimated the health risk for transported persons. The calculations of health risks were applied to the entire population persons transported in an individual automobile transport (IAT) in the Czech Republic. The results show that all age categories and especially children under two years of age are exposed to increased health risks arising from the BTEX produced by transportation.
Vliv těkavých organických látek z emisí výfukových plynů vozidel na lidské zdraví
Keywords: VOCs; BTEX; benzene; health; risk; assessment; VOCs; BTEX; benzen; zdraví; riziko; hodnocení